ANALISIS JARINGAN SOSIAL DALAM PENYEBARAN INFORMASI TERKAIT MENTAL HEALTH DI MEDIA SOSIAL: STUDI KASUS X - Syahid, Akhmad; Akhmad, Arfiah Nurbahri; Kurniawan (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
This study aims to analyze the spread of information about mental health on social media, particularly X, using a Social Network Analysis (SNA) approach. Data were collected from tweets containing keywords such as ‘mental health,’ ‘depression,’ ‘anxiety,’ and ‘MentalHealthAwareness,’ which were then analyzed using Gephi software on 1 October 2024. The results showed that social networks related to mental health discussions on X are fragmented but have strong internal connectivity. Retweets proved to be the main mechanism for extending the reach of information, while hashtags helped consolidate discussions. While there were no accounts that acted as the main link between groups, there were several influential accounts that played an important role in information dissemination. The main challenge in disseminating information related to mental health is ensuring the validity of information sources and overcoming network fragmentation. X has proven to be effective in disseminating information widely, but specialized strategies are needed to reduce the spread of misinformation. This research provides insights into how social media can be optimally utilized for more effective mental health campaigns. Keywords: Mental Health, Social Media, X, Social Network Analysis, Information Dissemination